Platelets made HLA deficient by acid treatment aggregate normally and escape destruction by complement and phagocytes in the presence of HLA antibodies. Issue 2 (7th October 2015) - Meinke, Stephan; Sandgren, Per; Mörtberg, Anette; Karlström, Cecilia; Kadri, Nadir; Wikman, Agneta; Höglund, Petter
Abstract : BACKGROUND: The presence of antibodies against HLA Class I can lead to platelet (PLT) transfusion refractoriness, that is, the repeated failure to achieve adequate posttransfusion PLT count increments. PLT refractoriness can be overcome by transfusion of HLA‐matched donor PLTs. A different approach is to remove HLA from the PLT surface using low pH. Previous case studies using HLA‐stripped PLTs showed encouraging but inconsistent results and lacked information on the biologic effects of acid treatment on PLT function as well as sensitivity to PLT destruction in the presence of HLA antibodies. STUDY DESIGN AND METHODS: PLTs prepared from buffy coats were stripped from HLA Class I using a brief incubation at pH 2.9. Kinetics of acid stripping, viability, phenotypic alterations, and sensitivity to complement‐mediated lysis and phagocytosis were determined by flow cytometry. Functional potential was evaluated using a multiplate analyzer. RESULTS: Acid‐treated PLTs were viable, upregulated activation markers normally and aggregated to a similar extent as untreated PLTs in response to stimulation with three natural agonists. Acid treatment removed 70% to 90% of HLA Class I complexes from the PLT surface, which led to complete protection from HLA antibody–mediated complement lysis and reduced monocyte‐mediated phagocytosis in the presence of anti‐HLA in vitro. CONCLUSION: Our study fills an important knowledge gap in how acid treatment affects PLT function and interactions with immune cells, paving the way for controlled clinical trials to evaluate acid‐treated PLTs as an alternative to HLA‐matched donors in PLT refractoriness.